Battery state of charge (SOC) assessment using KVI battery analyzer BA-2000 - Xu, Jia Sheng (Nanyang Technological University, 2022)
Estimating battery’s State of Charge (SOC) is essential when it comes to operation and usage of battery for various types of applications. An accurate SOC estimation will allow for understanding of battery performance, provide a “fuel gauge” indication for optimum control of charging, discharging process, and thereby prolonging battery life and battery safety. Several methods of SOC estimation are available today, and majority are based on battery modeling. Three types of well-known models are electrochemical models, analytical or mathematical models, and electrical circuit models. This final year project focuses on a SOC prediction method based on the linear relationship between SOC and thermodynamics data. The relationship is analyzed to evaluate the accuracy of this prediction method. This report outlines the background and motivation to investigate further into this SOC prediction method, literature review, the implementation framework and methodology, and the results achieved. An in-depth discussion into the results will follow. Lastly, the report will conclude with suggested future areas for improvement.